Laboratory monitoring of postvaccination measles immunity - A. A. Ereshchenko (Медицинская иммунология)
Measles vaccination In Russian Federation was introduced in 1967. It was assumed that the twodose vaccination regime would lead to a decrease in the incidence and elimination of measles. A number of studies have shown that up to 10% of individuals who received two doses of measles vaccine do not develop a specific humoral immunity, or do not maintain it at a protective level. This fact may contribute to gradual accumulation of persons susceptible for measles infection in the population, thus leading to emergence of new viral outbreaks in the future. The aim of this study was to perform dynamic monitoring of the post-vaccination measles immunity. The study involved 149 people. All the examined persons were divided into 2 groups. The group of comparison included persons, aged 19 to 51 years, in whom absence of measles immunity was serologically confirmed (n = 76). This group was twice vaccinated with live measles culture vaccine (NPO “Microgen”, Russia). Determination of IgG to measles virus was carried out 1 month after vaccination and revaccination. The control group consisted of persons with documented evidence of double immunization against measles virus, with laboratory-confirmed measles immunity (n = 73), aged 19 to 53 years. The comparative dynamics of development and contents of antibodies in the comparison-control groups were considered, with respect to the WHO age classification. Basic and postvaccinal dynamic determination of IgG to measles virus in serum was performed by ELISA using the “VectoKor-IgG” test system (Vector-Best, Novosibirsk). When analyzing the results of the study, it was noted that the level of measles immunity group in older persons from control group (over 45 years old) was initially higher, than in younger subjects. Among young people, the titers of specific measles antibodies reached the values of the control group of the corresponding age after the first vaccination, whereas the level of specific measles antibodies in older age group was significantly lower compared to the control group even after revaccination. A month after the first immunization, 4 people did not reach the protective level of anti-measles IgG. However, revaccination allowed them to form anti-measles immunity. In the course of our work, a case of non-response to vaccination was identified. Thus, our study showed a sufficient interindividual variability in humoral immune responses to measles vaccination.